The Neutrophil’s Choice: Phagocytose vs Make Neutrophil Extracellular Traps - Manfredi, Angelo A.; Ramirez, Giuseppe A.; Rovere-Querini, Patrizia; Maugeri, Norma (Frontiers in Immunology, 2018)
Neutrophils recognize particulate substrates of microbial or endogenous origin and react by sequestering the cargo via phagocytosis or by releasing neutrophil extracellular traps (NETs) outside the cell, thus modifying and alerting the environment and bystander leukocytes. The signals that determine the choice between phagocytosis and the generation of NETs are still poorly characterized. Neutrophils that had phagocytosed bulky particulate substrates, such as apoptotic cells and activated platelets, appear to be “poised” in an unresponsive state. Environmental conditions, the metabolic, adhesive and activation state of the phagocyte, and the size of and signals associated with the tethered phagocytic cargo influence the choice of the neutrophils, prompting either phagocytic clearance or the generation of NETs. The choice is dichotomic and apparently irreversible. Defects in phagocytosis may foster the intravascular generation of NETs, thus promoting vascular inflammation and morbidities associated with diseases characterized by defective phagocytic clearance, such as systemic lupus erythematosus. There is a strong potential for novel treatments based on new knowledge of the events determining the inflammatory and pro-thrombotic function of inflammatory leukocytes.